Analisis Perbandingan Standar yang Telah Ditetapkan Pemerintah dengan Kondisi di PT. XYZ dalam Pengelolaan Limbah Bahan Berbahaya dan Beracun Sebelum Diserahkan Ke Pihak Ke-3 - Yehezkiel, Roni Julianus; Sarungu, Selvia; Ratta, Elvis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. Pertamina is a company engaged in the Oil and Gas (MIGAS) industry engaged in drilling. This study analyzes how the existing conditions of B3 waste management resulting from drilling activities are carried out. The research uses the Guttman Scale Scoring method. The results of the study using the guttman scale scoring method show that the existing condition of B3 waste management at PT. Pertamina received a total percentage recapitulation of 45% in the